2015
DOI: 10.4067/s0718-58392015000100010
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Bemisia tabaci and activity of plant defense-related enzymes in genotypes of Capsicum annuum L.

Abstract: The whitefly Bemisia tabaci (Gennadius, 1889) is a major plant pest of horticultural crops from the families Solanaceae, Fabaceae and Cucurbitaceae in Neotropical areas. The exploration of host plant resistance and their biochemical mechanisms offers an excellent alternative to better understand factors affecting the interaction between phytophagous insect and host plant. We evaluated the survival of B. tabaci in landrace genotypes of Capsicum annuum L., and the activity of plant defense-related enzymes (chiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Ye et al (2012) studied that phloem-feeding herbivorous insects can trigger transcript accumulation of PPO and POD genes that deter further insect damage in rice. Recently, induction of PPO activity was found in whitefly herbivory in wild-type tobacco plants that can be correlated with NtPPO regulation of the present results (Zhao et al 2015) and PPO activity was recorded to be higher in whitefly-infested pepper genotypes than in non-infested genotypes (Latournerie-Moreno et al 2015). Earlier, PPO expression was found to be reduced in cotton by silencing of the PPO gene in response to beet armyworm, which implicated PPO as a component of defensive system against insects (Bhonwong et al 2009).…”
Section: Expression Analysis For Whitefly Infestationsupporting
confidence: 66%
“…Ye et al (2012) studied that phloem-feeding herbivorous insects can trigger transcript accumulation of PPO and POD genes that deter further insect damage in rice. Recently, induction of PPO activity was found in whitefly herbivory in wild-type tobacco plants that can be correlated with NtPPO regulation of the present results (Zhao et al 2015) and PPO activity was recorded to be higher in whitefly-infested pepper genotypes than in non-infested genotypes (Latournerie-Moreno et al 2015). Earlier, PPO expression was found to be reduced in cotton by silencing of the PPO gene in response to beet armyworm, which implicated PPO as a component of defensive system against insects (Bhonwong et al 2009).…”
Section: Expression Analysis For Whitefly Infestationsupporting
confidence: 66%
“…Leaf colour: A total of three matured leaves were selected randomly from each genotype and scored using RHS colour chart (The Royal Horticultural Society, Fifth edition, 2007) and scoring was done according to the colour intensity (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Trichomesmentioning
confidence: 99%
“…Similarly Firdaus et al (2011) [5] reported that C. annuum accessions showed highly resistant reaction in no-choice and free choice tests. Genotypes such as Chawa, Blanco, Maax and X'catic were found less susceptible to B. tabaci (Ballina-Gomez et al, 2013) [8] and Amaxito, Tabaquero, and Simojovel showed resistance to whitefly (Latournerie-Moreno et al, 2015) [9] . Genotypes IAC-1544, IAC-1545 and IAC-1579 showed antibiosis mechanisms for whitefly (Pantoja et al, 2017) [10] and the genotypes CA 9, CA28 and ACC 05 have displayed strong antiemetic and antibiotic effect against B. tabaci (Jeevanandham et al, 2018) [11] can be good source of resistance.…”
Section: Nymphal Populationmentioning
confidence: 99%
“…Resistance to B. tabaci in landrace, semi-wild and commercial genotypes has been evaluated in various vegetable crop species, such as soybean (Glycine max) (Cruz and Baldin, 2017), tomato (Solanum lycopersicum) (Oriani et al, 2011;Rakha et al, 2017), eggplant (Solanum melongena) (Hasanuzzaman et al, 2016), melon (Cucumis melo) (McCreight et al, 2017), cassava (Manihot esculenta) (Mwila et al, 2017) and pepper (Capsicum annuum) (Ballina-Gomez et al, 2013;Firdaus et al, 2011;Jeevanandham et al, 2018). In genotypes of C. annuum different degrees of resistance to B. tabaci have been observed (Ballina-Gomez et al, 2013;Firdaus et al, 2011;Latournerie-Moreno et al, 2015). The wide genetic variation of C. annuum offers an opportunity to explore host plant resistance and to study the plant traits that influence such resistance.…”
Section: Introductionmentioning
confidence: 99%